COMPUTATIONAL ANALYSIS OF HIP PROSTHESIS: IMPACT OF SHAPE AND MATERIAL ON MECHANICAL PERFORMANCE - Nikam, Nishant; Shenoy B, Satish; G Keni, Laxmikant; Shetty, Sawan; Bhat N, Shyamasunder; K N, Chethan (Journal of Applied Engineering Science, 2025)
Hip implants play a crucial role in restoring mobility and reducing pain in patients with hip joint disorders. The design and material selection of the implant stem significantly influence its mechanical performance and longevity. This study presents a comparative finite element analysis of circular and rectangular hip implant stems to evaluate their structural behaviour under static loading conditions. The implant stems were modeled using CREO 11.0 and analysed using Ansys 2023 R2, with a load of 2300 N applied to simulate real-world conditions. Two materials—Cobalt Chromium (CoCr) and Ti–6Al–4V alloys—were considered to assess their mechanical properties. The results indicate that rectangular stems exhibited lower total deformation, von Mises stress, and strain compared to circular stems, making them structurally superior. Among the materials analysed, CoCr demonstrated better mechanical performance, reducing stress concentration and potential failure risks. Additionally, metal-on-metal (MoM) configurations showed enhanced durability over metal-on-polyethylene (MoPE). These findings suggest that a rectangular CoCr stem in a MoM configuration is optimal for improving implant longevity and reducing revision surgery rates. The study underscores the importance of optimized implant geometry and material selection in total hip arthroplasty. Future research should explore dynamic loading conditions and patient-specific implant designs to enhance clinical outcomes further.
Keywords: finite element analysis, hip implants, total hip replacement, osteoarthritis, aseptic loosening